Permanent damage of the sciatic nerve in an 8-year-old girl with newly diagnosed type 1 diabetes. (2nd January 2020) - Giza, Styliani; Litou, Eleni; Kotanidou, Eleni P.; Kleisarchaki, Angeliki N.; Koliatos, Panagiotis; Tzirtzipis, Tasos; Tsinopoulou, Vasiliki Rengina; Tychalas, Athanasios; Evangeliou, Athanasios; Galli-Tsinopoulou, Assimina
ABSTRACT: Neuropathy, a complication of type 1 diabetes (T1D), is a heterogeneous group, and chronic polyneuropathy is the most common form in adults. Αn 8-year-old girl admitted with severe diabetic ketoacidosis was diagnosed with T1D. She was managed with intravenous fluids and insulin and was subsequently commenced on multiple daily subcutaneous injections of insulin. On the 7th day of hospitalisation, a right foot drop with sensory loss on the dorsal surface and cellulitis were detected and the latter responded to intravenous antibiotics. Electrophysiology demonstrated reduced nerve conduction velocity indicative of severe axonal damage of the sciatic nerve (SN). Physiotherapy along with vitamins B6 and B12 and magnesium were prescribed. Twelve months later there was no sign of clinical improvement and the selective damage of the SN was deemed to be permanent. Peripheral neuropathy can occur in children with newly diagnosed T1D. Abbreviations : DKA: diabetic ketoacidosis; DN: diabetic neuropathy; HbA1c: glycated haemoglobin; MRC: Medical Research Council; MRI: magnetic resonance imaging; PICU: paediatric intensive care unit; SN: sciatic nerve; T1D: type 1 diabetes